Knowledge, Attitude, and Preventive Practices towards Sexually Transmitted Infections among Preparatory School Students in West Gojjam Zone, Ethiopia. (12th May 2020) - Kassie, Ayalnesh Asmamaw; Gudayu, Temesgen Worku; Araya, Bilen Mekonnen
Abstract : Background . Sexually transmitted infections are major public health concerns that mostly affect adolescents and young people. Hence, the aim of this study was to assess students' knowledge, attitude, and preventive practice towards sexually transmitted infections and the associated factors. Methods . A school-based cross-sectional study was conducted from October 24 to November 4, 2018. A sample size of 845 was calculated and a 1-stage sampling technique was employed. Data were collected through a self-administered questionnaire. The data were entered into Epi-Info 7.2 and analyzed using IBM SPSS version 25 software. The descriptive result was presented in text, figure, and tables. Also, bivariate and multivariable logistic regression analyses were done to identify associated factors. Then the adjusted odds ratio and its 95% confidence interval were computed. And a p value of <0.05 was considered to assert statistical significance. Results . Half of the respondents (50.5%) had good knowledge on sexually transmitted infections. Also, 46.4% of students had a good preventive practice. However, only 38.4% of students had an appropriate attitude towards sexually transmitted infections. Being a male (AOR: 1.58 (95% CI: (1.19, 2.09)) and having employed father (AOR: 1.97 (95% CI: (1.18, 3.30)) predicted good knowledge. Similarly, secondary and above level of paternal education (AOR: 2.16 (95% CI: (1.28, 3.64)) and having a farmer father (AOR: 1.77 (95% CI: (1.04, 3.02)) predicted appropriate attitude. Predictors of preventive practices included elder age (AOR: 2.33 (95% CI: (1.27, 4.28)), never had sexual intercourse (AOR: 1.44 (95% CI: (1.07, 1.94)), and having good knowledge on STIs (AOR: 1.53 (95% CI: (1.16, 2.02)). Conclusion . The proportion of students that had good knowledge, appropriate attitude, and good preventive practice towards STIs were low. Personal and parental factors predicted students' knowledge, attitude, and preventive practices. Hence, creating awareness need to be strengthened.